“I rest. your pore troublesome sister”: An Edition of the Letters of Lettice Kinnersley, and an Examination of Syntactic Sensitivity in the Application of Punctuation - Ruohomaa, Sauli (My University, 2017)
This thesis has two objectives. The first is to create an edition of the letters of Lettice Kinnersley, written circa 1595-1622. The letters belong to the Folger Shakespeare Library. The edition provides original transcriptions of the letters, as well as a glossary. In addition to this, it also discusses the handwriting practices of the 16th and 17th centuries with a focus on the qualities of the individual hands used in the letters. There are also chapters on abbreviation practices and punctuation marks. The transcriptions are a contribution to the Early Modern Manuscripts Online database maintained by the Folger Shakespeare Library. The purpose of the database is to provide transcriptions of historical English texts for the purpose of research. The transcriptions I provide are semi-diplomatic and remain fairly faithful to the appearance of the original texts. Editorial additions have been clearly indicated as such. The second objective is to examine if Lettice Kinnersley’s punctuation system is functionally syntactic. The transcriptions created for the edition are used to conduct an analysis of the punctuation in the materials. During the time the letters were written, punctuation was commonly applied as a means to imitate qualities of spoken language. A new punctuation method that was sensitive to syntax was beginning to take hold however. My materials exhibit punctuation that appears to be sensitive to syntax, and as such I conducted a grammatical analysis of the punctuation. My analysis utilized a grammatical framework to explain the punctuation method used by Lettice Kinnersley and her scribe. In addition, the punctuation methods of Lettice and her scribe were compared to a few select theoretical accounts of ‘correct’ usage of punctuation that were written in the 16th and 17th centuries. The theoretical accounts represented the new, syntactic method of punctuation. If a reasonable amount of inconsistency in practice is forgiven, the punctuation in my materials appears to indicate syntactic structures. This is notable because women’s punctuation has previously been deemed as particularly unruled. My results would suggest that applying a grammatical method of analysis in the case of some female letter writers might prove this assertion wrong.